SAT0595 DIRECT COMPARISON OF CERTOLIZUMAB PEGOL, ABATACEPT AND BIOSIMILAR INFLIXIMAB IN PATIENTS WITH RHEUMATOID ARTHRITIS TREATED IN ROUTINE CARE. OBSERVATIONAL DATA FROM THE DANISH DANBIO REGISTRY ANALYZED LIKE A RANDOMIZED CLINICAL TRIAL. (June 2019) - Grøn, Kathrine; Glintborg, Bente; Nørgaard, Mette; Mehnert, Frank; Östergaard, Mikkel; Dreyer, Lene; Krogh, Niels Steen; Bjørner, Jakob B.; Hetland, Merete L.
Abstract : Background: Nationwide Danish guidelines regarding RA patients (pts) initiating bDMARDs are issued approximately annually. For bio-naïve pts on concomitant methotrexate (MTX) the recommended drugs (year, recommended compliance) were: certolizumab pegol(CTZ)(2013-2014, 80%)/abatacept(ABA)(2014-2015, 80%)/biosimilar infliximab(CT-P13)(2015-2016, 50%). We hypothesized that the guidelines could be perceived as a surrogate randomization tool where calendar-time rather than patient-specific factors defined choice of bDMARD. Objectives: To assess compliance to guidelines (justifying the assumption of surrogate randomization) and compare effectiveness of CTZ/ABA/CT-P13 in Danish RA patients treated according to guidelines. Methods: Observational cohort study analyzed like a randomized clinical trial (RCT, intention-to-treat). RA patients were identified in DANBIO. Compliance in each calendar period was defined as number of pts adherent to guideline/numbers of all bio-naïve pts initiating bDMARD+MTX. Outcomes were DAS28-remission-rates (at 6 and 12-months) and one-year retention rates, compared across treatments (confounder-adjusted multivariable logistic and Cox regression analyses). Results: Compliance to guidelines was 70%/65%/59%, and 776 patients were included (CTZ/ABA/CT-P13: 336/215/225). Baseline characteristics were similar across drugs. DAS28 remission-rates after 6 and 12 months were: 37%/34%/44% and 37%/33%/36%, respectively. Adjusted odd ratios for achieving DAS28 remission were at 6 months: 0.96(95% CI: 0.6;1.5) for ABA and 1.38(0.9;2.1) for CT-P13; 12 months: 0.74(0.5;1.2) and 0.96(0.6;1.5), CTZ reference drug(figure). The adjusted hazard ratios for withdrawal were 1.16(95% CI: 0.84;1.60) for ABA and 0.83 for CT-P13(0.59;1.17)(table). Variables are median (IQR) unless otherwise mentioned. *age, gender, DAS28, HAQ, smoking, CCI Abbreviations: CCI: Charlson Comorbidity Index: CI: confidence intervals, DAS28: Disease Activity Score of 28 joints, HAQ: Health assessment questionnaire Conclusion: Compliance to guidelines was high. Direct comparison showed that remission and retention rates were highest for CT-P13, intermediate for certolizumab and lowest for abatacept. Results should, however, be interpreted with caution due to wide CIs and risk of residual confounding. Acknowledgement: Thanks to Laura Köcher from Karolinska Institutet, Stockholm, Sweden for help with the figure Disclosure of Interests: Kathrine Grøn Grant/research support from: BMS, Bente Glintborg Grant/research support from: Biogen, Pfizer, AbbVie, Mette Nørgaard: None declared, Frank Mehnert: None declared, Mikkel Östergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Lene Dreyer Consultant for: MSD, UCB and Janssen Pharmaceuticals, Speakers bureau: MSD, UCB and Janssen Pharmaceuticals, Speakers bureau: UCB, MSD, Eli Lilly and Janssen Pharmaceuticals., Niels Steen Krogh: None declared, Jakob B. Bjørner Employee of: Optum, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen, Pfizer, Consultant for: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck, Samsung Bioepis